Recent liquid chromatographic approaches and developments for the separation and purification of carbohydrates. Issue 24 (2nd June 2017) - Nagy, Gabe; Peng, Tianyuan; Pohl, Nicola L. B.
Abstract : This review highlights current techniques for carbohydrate purification and identifies research gaps. Abstract : Carbohydrate purification remains a bottleneck in securing analytical standards from natural sources or by chemical or enzymatic synthesis. This review highlights the scope and remaining limitations of recent approaches and methods development in liquid chromatography for robust and higher-throughput carbohydrate separation and isolation.